1979
DOI: 10.1111/j.1399-3054.1979.tb01677.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of Rice Tungro Virus Disease: Involvement of Abscisic Acid‐Like Substance in Susceptible Host‐Virus Interactions

Abstract: Stunting was severe in susceptible rice (Oryza saliva L.) cultivar ‘Taichung Native 1’ infected with tungro virus (RTV) compared to less‐susceptible cultivar ‘IR 20’. The senescence of detached leaves of RTV‐infected susceptible cultivar incubated in water in dark was accelerated compared to the healthy leaves as measured by the loss of total chlorophyll content. The transpiration rate of RTV‐infected leaves of the susceptible cultivar was much lower than the healthy and RTV‐infected leaves of the less‐suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1982
1982
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Increases of proline in the leaves of tungro-diseased plants thus occurs in the absence of external water stress. Furthermore, ABA-like activity substantially increases in leaves of a RTV sensitive rice cultivar in response to the virus infection (Mohanty et al, 1979), This suggests that proline increase is mediated by ABA, whose endogenous concentration may increase, presumably due to the trigger from the virus-induced internal water stress. Indeed, also enhanced leaf senescence, inhibition of transpiration (Mohanty et al, 1979) and…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Increases of proline in the leaves of tungro-diseased plants thus occurs in the absence of external water stress. Furthermore, ABA-like activity substantially increases in leaves of a RTV sensitive rice cultivar in response to the virus infection (Mohanty et al, 1979), This suggests that proline increase is mediated by ABA, whose endogenous concentration may increase, presumably due to the trigger from the virus-induced internal water stress. Indeed, also enhanced leaf senescence, inhibition of transpiration (Mohanty et al, 1979) and…”
Section: Resultsmentioning
confidence: 95%
“…slowed down the proline accumulation, ABA synthesized in response to virus infection mediates proline accumulation in the tungro disease syndrome, since rice cuitivars varying in their reaction to RTV differed in their efficiency to synthesize ABA-Hke substances when infected with RTV (Mohanty et al, 1979), However, the sensitivity of our rice cultivars to the virus, and their ability to gain proline during normal senescence or during senescence accelerated by exogenous ABA (2 X lO^M), are evidently not correlated with each other.…”
Section: Cultivarmentioning
confidence: 83%
See 1 more Smart Citation
“…Measurements of the (3-inhibitor complex of growthretarding substances, of which ABA is a major component (132), showed unchanged activity after TMV infection of tobacco (132), but increased activity in PMV-infected lupin (151) and rice tungro virus (RTV)-infected rice (95) . In experiments where ABA was measured by physical methods, infection of cucumber with cucumber mosaic virus (CMV) was reported to cause no change (9), but other workers reported a three-fold increase (1) .…”
Section: A Bscisic Acidmentioning
confidence: 99%
“…Salicylic acid and jasmonic acid/ethylene orchestrate response against (hemi)biotrophic pathogens and necrotrophic pathogens, respectively. The fi rst study suggestive of the involvement of ABA in disease response came in 1979 (Mohanty et al 1979 ) where bioassays revealed a significantly higher ABA-like activity from the extracts of the rice tango virus (RTV)-infected susceptible rice cultivar than that of the less-susceptible cultivar. There were studies that reported that ABA negatively affects the disease resistance (Rezzonico et al 1998 ;McDonald and Cahill 1999 ;Audenaert et al 2002 ).…”
Section: Role Of Aba In Biotic Stress Tolerance Of Plantsmentioning
confidence: 99%